1992
DOI: 10.2175/wer.64.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Advective transport in activated sludge flocs

Abstract: The liquid flow through activated sludge floes from fullscale conventional treatment plants was evaluated on the basis of the information obtained from settling tests. In the samples of the mixed liquors studied, only a part of the activated sludge flocs was found permeable to fluid drainage. Basically, small flocs were not permeable but all the flocs in the size range from 100‐150 μm showed different degrees of permeability. The permeability of flocs increased with an increase in the dynamic sludge age and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 15 publications
3
39
0
Order By: Relevance
“…In support of this result, Li and Ganczarczyk (1992) stated that sludge flocs may be permeable, depending on their size and the plant operating conditions. They also suggested that advective transport through channels in the sludge flocs could be the main mass transfer mechanism, which could explain the absence of transport limitations in the flocs.…”
Section: Physicochemical Phenomena: Diffusion Of Substrate Into Activmentioning
confidence: 85%
“…In support of this result, Li and Ganczarczyk (1992) stated that sludge flocs may be permeable, depending on their size and the plant operating conditions. They also suggested that advective transport through channels in the sludge flocs could be the main mass transfer mechanism, which could explain the absence of transport limitations in the flocs.…”
Section: Physicochemical Phenomena: Diffusion Of Substrate Into Activmentioning
confidence: 85%
“…Theoretical work has been conducted to characterize the permeability and the reduction factors (Brinkman, 1947;Happel, 1958;Dullien, 1992;Alder, 1981;Veerapaneni and Wiesner, 1996;Vanni, 2000). In addition, many conventional column experiments (Li and Ganczarczyk, 1992;Li and Logan, 1997;Li et al, 2003) have been carried out to elucidate the inherent relationship between the reduction factor and the permeability of the particles. However, these experiments only predicted the floc permeability from the floc terminal velocity and other factors and could not provide detailed information about the hydrodynamics in the creeping flow field.…”
Section: Discussionmentioning
confidence: 99%
“…Aggregates formed by bacteria are known to be highly fractal (Meakin, 1988;Li and Ganczarczyk, 1989;Jiang and Logan, 1991), with fractal dimensions depending on the type of floc, physical conditions such as fluid shear rate, and the mechanism of floc formation (Logan and Wilkinson, 1991;Zahid and Ganczarczyk, 1994;Li et al, 2003). The open structure of highly porous and fractal aggregates can allow intra-aggregate flow through the flocs, resulting in their settling velocity being appreciably faster than that predicted for impermeable spherical particles (Li and Ganczarczyk, 1992;Johnson et al, 1996;Li and Yuan, 2002). Biological flocs produced in activated sludge reactors are highly porous and fractal (Li and Ganczarczyk, 1990;Lee et al, 1996;Li and Yuan, 2002), but the flow through the floc is not large enough to affect their settling behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Biological flocs produced in activated sludge reactors are highly porous and fractal (Li and Ganczarczyk, 1990;Lee et al, 1996;Li and Yuan, 2002), but the flow through the floc is not large enough to affect their settling behavior. However, floc permeability can affect mass transport rates to bacteria inside the floc, even under conditions where it does not affect settling velocity (Logan and Hunt, 1988;Li and Ganczarczyk, 1992;Tsou et al, 2002;Li et al, 2003).…”
Section: Introductionmentioning
confidence: 99%